l
Evaluate the following logarithmic expression
logof200
Evaluate logof200
We'll do bases e and 2-10
The formula for the change of base rule in logb(x) is as follows:
logb(x) = | Ln(x) |
Ln(b) |
loge(200) = | Ln(200) |
Ln(e) |
Ln(e) = 1
loge(200) = 5.298317366548
The formula for the change of base rule in logb(x) is as follows:
logb(x) = | Ln(x) |
Ln(b) |
log2(200) = | Ln(200) |
Ln(2) |
log2(200) = 7.6438561897747
The formula for the change of base rule in logb(x) is as follows:
logb(x) = | Ln(x) |
Ln(b) |
log3(200) = | Ln(200) |
Ln(3) |
log3(200) = 4.8227363021502
The formula for the change of base rule in logb(x) is as follows:
logb(x) = | Ln(x) |
Ln(b) |
log4(200) = | Ln(200) |
Ln(4) |
log4(200) = 3.8219280948874
The formula for the change of base rule in logb(x) is as follows:
logb(x) = | Ln(x) |
Ln(b) |
log5(200) = | Ln(200) |
Ln(5) |
log5(200) = 3.2920296742202
The formula for the change of base rule in logb(x) is as follows:
logb(x) = | Ln(x) |
Ln(b) |
log6(200) = | Ln(200) |
Ln(6) |
log6(200) = 2.9570472251115
The formula for the change of base rule in logb(x) is as follows:
logb(x) = | Ln(x) |
Ln(b) |
log7(200) = | Ln(200) |
Ln(7) |
log7(200) = 2.7227965120179
The formula for the change of base rule in logb(x) is as follows:
logb(x) = | Ln(x) |
Ln(b) |
log8(200) = | Ln(200) |
Ln(8) |
log8(200) = 2.5479520632582
The formula for the change of base rule in logb(x) is as follows:
logb(x) = | Ln(x) |
Ln(b) |
log9(200) = | Ln(200) |
Ln(9) |
log9(200) = 2.4113681510751
The formula for the change of base rule in logb(x) is as follows:
logb(x) = | Ln(x) |
Ln(b) |
log10(200) = | Ln(200) |
Ln(10) |
log10(200) = 2.301029995664